Use the effect of some exercises for rehabilitation of injuries of the knee joint and its impact on some physical abilities and the achievement of the effectiveness of long jump for students - RAZZAQ JAWAD, BAYDAA; JAMEEL HUSSEIN AL_ SAADI, ISRAA; ISAM ABDULAMEER, FARAH (International Journal of Psychosocial Rehabilitation, 2020)
The researchers extracted some aspects of benefit, the most important of the research approach, and the variables that must be measured, such as the dynamic range, the fixed muscle strength, and the accompanying surroundings in order to follow the change in the limb to be treated, and also previous studies helped in the diversity of methods of physical and motor measurements, choosing the most appropriate types with the available capabilities. Also, previous studies the researcher assisted in increasing the scientific result to achieve the aim of the study to discuss the results and reach scientific explanations . The researcher hopes to add new things through the use of a proposed rehabilitation program to contribute to providing an effective way to rehabilitate the knee joint by focusing on therapeutic exercises accompanied by natural means in order to return the injured person to his normal state as soon as possible.